Hubungan antara Kontrol Diri dengan Prokrastinasi dalam Menyelesaikan Skripsi pada Mahasiswa Universitas Muria Kudus - Aini, Aliya Noor; Mahardayani, Iranita Hervi (Jurnal Psikologi: PITUTUR, 2011)
This study aims to examine the relationship between  self-control  with  procrastination  in finishing the final project on college students. In this study the subjects of research is the student at Universitas Muria Kudus, with a purposive sampling. That is based on a characteristics are students at the Universitas Muria Kudus who already  took  a  final  project  at  least  two semesters  and  take  the  achieve  study  period more than 8 semesters. Results of analysis of data obtained from both the correlation coefficient rxy = 0.401 with a p = 0.000 (p <0.01) this means there is a very significant negative relationship between self-control  with  procrastination  in  completing  the final  project  on  student  at  Universitas  Muria Kudus.  Effective  contribution  of  self-control variables on procrastination in finishing the final project are 16.08%.